2007
DOI: 10.1103/physrevlett.98.216804
|View full text |Cite
|
Sign up to set email alerts
|

Electron Leakage and Double-Exchange Ferromagnetism at the Interface between a Metal and an Antiferromagnetic Insulator:CaRuO3/CaMnO3

Abstract: Density-functional electronic structure studies of a prototype interface between a paramagnetic metal and an antiferromagnetic (AFM) insulator (CaRuO(3)/CaMnO(3)) reveal the exponential leakage of the metallic electrons into the insulator side. The leaked electrons in turn control the magnetism at the interface via the ferromagnetic (FM) Anderson-Hasegawa double exchange, which competes with the AFM superexchange of the bulk CaMnO3. The competition produces a FM interfacial CaMnO3 layer (possibly canted); but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 25 publications
(26 reference statements)
10
47
0
Order By: Relevance
“…4 Thereafter, density-functional theory calculations and spectroscopic studies revealed that a small leakage of itinerant electrons from the CRO can induce weak FM via the doubleexchange (DE) in a few interfacial unit-cells of CMO. 5,6 The interfacial FM was also confirmed by the observed EB in CMO/CRO SLs. 7 On the other hand, the stacking of La 0.67 Sr 0.33 MnO 3 (LSMO) and SrRuO 3 (SRO), both are ferromagnetic-metal at low temperature (T), may constitute another interesting example of the system, 8 which is characterized by an AF interlayer coupling.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…4 Thereafter, density-functional theory calculations and spectroscopic studies revealed that a small leakage of itinerant electrons from the CRO can induce weak FM via the doubleexchange (DE) in a few interfacial unit-cells of CMO. 5,6 The interfacial FM was also confirmed by the observed EB in CMO/CRO SLs. 7 On the other hand, the stacking of La 0.67 Sr 0.33 MnO 3 (LSMO) and SrRuO 3 (SRO), both are ferromagnetic-metal at low temperature (T), may constitute another interesting example of the system, 8 which is characterized by an AF interlayer coupling.…”
supporting
confidence: 53%
“…23,26,27 As the ultrathin LCMO was sandwiched between CRO layers, the charge transfer from CRO layer into the interfacial LCMO was supposed to take place. [4][5][6][7][8] The supplied mobile carriers in the interfacial region would facilitate the DE, thus depressing the nucleation of the AF phase or the tendency to EPS. Such a scenario is analogous to the case for CRO/CMO SLs, where the metallic CRO also acts as a donator and the mobile electrons leaked into the CMO can induce an interfacial canted FM via the DE.…”
mentioning
confidence: 99%
“…1). This scenario was supported by density functional calculations 16 and by a detailed spectroscopic study 17 . However, the magnetization profile determined by reflectometry with circularly polarized x-rays 17 revealed that the ferromagnetic magnetization penetrates more deeply into the CaMnO 3 layers than predicted by the ab-initio theory, possibly as a consequence of the formation of magnetic polarons that have also been invoked to explain experiments on bulk doped CaMnO 3 .…”
Section: Introductionmentioning
confidence: 60%
“…At oxide interfaces, charge transfer can be driven by a difference in chemical potential or by screening of local dipoles. Charge transfer can alter the B -site valence states near the interface, enabling magnetic order that is distinct from either constituent, for instance leading to ferromagnetism confined to the interface between two insulating antiferromagnets [Salvador et al ., 1999; Lin et al ., 2006; Santos et al ., 2011] or ferromagnetism from a paramagnetic metal and antiferromagnetic insulator [Takahashi et al ., 2001; Nanda et al ., 2007; Freeland et al ., 2010; He et al ., 2012]. The spatial extent of the interfacial magnetism closely matches that of the charge transfer length scale, which is generally quite short, around 0.4 nm to 2 nm [Santos et al ., 2011; Grutter et al ., 2013; Hoffman et al ., 2013], owing to both the large dielectric constant and significant carrier concentration (charge density) that complex oxides often support [Ahn et al ., 2006].…”
Section: Emergent Magnetism At Interfacesmentioning
confidence: 99%